The evolution of Paleolithic technologies - Kuhn, Steven L., 1956- author.
1 online resource (ix, 419 pages)
Keywords: "The Evolution of Paleolithic Technologies provides a novel perspective on the long-term development of Paleolithic technologies and their makers, one that is more in keeping with contemporary Darwinian thinking about human evolution. Members of the human lineage have been producing stone tools for more than 3 million years. These artifacts provide key evidence for important evolutionary developments in hominin behavior and cognition. Avoiding conventional approaches based on progressive stages of development, this book instead examines global trends in six separate dimensions of technological behavior between 2.6 million and 10,000 years ago. Combining these independent trends results in both a broader and a more finely-punctuated perspective on key intervals of change in hominin technological behavior. To draw this picture together, behavioral, cognitive, and demographic implications of developments in material culture and technological procedures are highlighted at seven key intervals during the Pleistocene. Scholars and archaeologists interested in the development of Palaeolithic technologies will find this book invaluable. It will also be of interest to anthropologists and students of human evolution and behavioral development in prehistory"--